Education on the Investment Acquisition and Payment Cycle to Strengthen the Internal Control System at CV Citra Panca Mandiri - Idra Wahyuni; Adnan Dwi Susanto; Sitti Sahria; A. Arfan; Arya Saputra Syam; Wahyuni (Masterpiece, 2026)
This study examines the implementation of revenue recognition and construction contract cost recognition under PSAK 72 at PT Wijaya Karya (Persero) Tbk, a leading state-owned construction company listed on the Indonesia Stock Exchange. The research aims to evaluate the extent to which the company’s accounting practices comply with PSAK 72 in recognizing revenue from contracts with customers and matching contract costs with recognized revenue. A qualitative descriptive approach was employed using document analysis of secondary data obtained from the company’s annual reports, audited financial statements, accounting policies, and relevant academic literature. The collected data were analyzed by comparing the company’s accounting treatment with the recognition, measurement, and disclosure requirements prescribed by PSAK 72. The findings reveal that the adoption of PSAK 72 has not fundamentally changed revenue recognition for the company’s core construction contracts because revenue continues to be recognized over time using the cost-to-cost percentage-of-completion method, which satisfies the standard’s performance obligation criteria. Nevertheless, challenges remain in estimating and allocating construction contract costs, particularly in the recognition of contract assets, inventory classification, and cost matching, potentially affecting the reliability of financial reporting. The study demonstrates that compliance with PSAK 72 extends beyond revenue recognition and requires robust cost estimation, contract management, and internal control systems to ensure faithful financial reporting. This research contributes to the literature by providing empirical evidence on PSAK 72 implementation in Indonesia’s construction sector and offers practical recommendations for enhancing accounting quality, transparency, and accountability in long-term construction contracts.